An Assessment of Third Grade Medical Students’ Level of Knowledge and Attitudes About Family Planning - Tutar Çölgeçen, Eda Fulden; Çölgeçen, Kadir (Turkey Health Literacy Journal, 2022)
Objective: The aim of this study was to determine the knowledge and attitudes of third year medical school students in Turkey about family planning.Method: 51 students out of 159 students who are in the third year of a medical school in Turkey voluntarily participated in our study. Data were collected from the participants through an online questionnaire consisting of 20 questions to evaluate their sociodemographic characteristics, knowledge and attitudes about family planning.Results: The ages of 51 students participating in the study were between 19 and 25, with an average age of 21.14 and a median of 21.Of the participants, 28 (54.9%) were female students and 23 (45.1%) were male students. While 45 (88.2%) students got the definitionof family planning correct by ticking the option “Families have as many children as they want and can take care of”, 6 (11.7%) studentsticked the other propositions. The most well-known modern methods were oral contraceptives with 37 (72.5%), intrauterine deviceswith 33 (64.7%) and condom with 29 (56.9%). The most well-known traditional methods were coitus interruptus with 34 (66.7%), vaginaldouching with 28 (54.9%) people.Discussion and Conclusion: This study reveals that although the 3rd year medical faculty students have not yet received training on family planning methods, their level of knowledge is not insufficient, but there is a need for training on this subject.
Keywords: Family Planning, Medical Students, Contraception, Knowledge and Attitude